Inovasi Pembelajaran dalam Membentuk Karakter Siswa di Era Digital - Yanuar Dila Nur Alifa; Mita Siti Afifah; Robi Agisna; Usnida Juaneka Verawati; M Saifudin Zuar (Civiliza Publishing, 2023)
Innovation in learning has an important role in balancing the changes that exist in Indonesia. These changes cannot be separated from the collaboration between the younger generation and the adult generation. Every change that develops will definitely give birth to new findings that can provide convenience and will cause several problems. This study aims to describe how learning innovation shapes student character in the digital era. This study used a qualitative research method with a literature study approach. The result is that learning in the digital era has a rapid flow of progress, technology has become a new facility and innovation that educators must master and integrate into learning. Education is one of the most important breakthroughs in overcoming the characters that are happening in the digital era, in the process students can learn to manage time and use technology responsibly. Based on the data analysis, it can be concluded that learning innovation by utilizing technology is very important in increasing understanding and shaping student character in the digital era